Pipisin, the Pangolin - Shaw, RachelLouise; Shaw, Rachel Louise (Makati City The Bookmark, Inc., 2015)
"Pipisin is a young Philippine pangolin. He's living on his own for the first time and is struggling to find his favorite food: ants. He's scared of lots of things. When he hears strange noises or comes across animals, he rolls into a ball until he feels safe again. Then one day, he's the only one who can help other animals that are trapped and he has to be brave. All the animals Pipison meets are found in the island of Palawan.
Keywords: Pangolins -- Juvenile fiction; Nursery rhymes, English; Children's stories, Philippine (English).